Strategi Pemanfaatan Event Hiburan Musik, Kualitas Pelayanan, Dan Cita Rasa Kopi Terhadap Minat Berkunjung Generasi Z Di Kalamera Coffee Space Medan - Citra Indah Octavia; Indawati Lestari (Journal of Innovative and Creativity, 2025)
This study aims to analyze the experience-based marketing strategy implemented by Kalamera Coffee Space Medan, specifically focusing on the simultaneous and partial influence of Music Entertainment Events, Service Quality, and Coffee Taste on the Visiting Interest of Generation Z. Gen Z, known for their preference for authentic experiences and social interaction, forms the core focus of this research, given the fierce competition in the Coffee Shop industry. The research employed an associative quantitative approach by distributing questionnaires to 120 Gen Z respondents who are visitors of Kalamera Coffee Space. Data analysis utilized Multiple Linear Regression, t-test (Partial), F-test (Simultaneous), and the Coefficient of Determination (R²), after ensuring the model met classical assumptions. The findings reveal that partially, the Music Entertainment Event Strategy, Service Quality, and Coffee Taste each have a positive and significant influence on Gen Z's Visiting Interest. Service Quality (t=7.823) provides the largest partial influence, followed by Music Entertainment Events (t=6.904), and the unique Karo Coffee Taste (t=5.838). Simultaneously, all three variables were found to have a highly significant influence (F=126.055). The combined contribution of this experience-based marketing strategy is highly dominant, explaining 76.5% of the variation in Gen Z's Visiting Interest, with the remaining 23.5% attributed to external factors outside the model. This conclusion underscores the importance of a holistic multisensory approach in captivating and retaining the loyalty of Gen Z consumers.